Analisis Evaluasi Pembelajaran IPA Terpadu Dimasa “Sekolah Dari Rumah” - Muh Yunus; Gustina; Eka Fitriana Hamsyah; Andi Nur Samsi (Universitas Tadulako, 2021)
This research is a qualitative descriptive study conducted in May – June 2021 with the aim of seeing how the learning process takes place at school and how flexible learning is during school from home. The population in this study are all science teachers in South Sulawesi. Sample selection is done by area sampling. The research instrument was in the form of a questionnaire that had to be filled out by the science teacher through a google form distributed through the MGMP IPA Whatsapp group in several districts in the province of South Sulawesi. A total of 18 question items contained in the questionnaire. The data analysis technique used is to describe and describe the answers of the respondents. The research that has been done shows that there are still many teachers who have difficulty evaluating learning (cognitive, psychomotic, and affective). As many as 27,57% of teachers said it was very difficult to assess the cognitive aspect, 16,97% of teachers said it was very difficult to assess the affective aspect, and 20.3% of teachers said it was very difficult to assess the psychomotor aspect. Difficulties in evaluating learning are constrained by several things. The main obstacle that most often arises is inadequate children's learning facilities, starting from the inability of parents to buy communication tools for online learning to network constraints which almost some areas feel the impact.